Assessment of Cardiac Autonomic Function Tests: A Perspective to Possible Predictor of Outcome in COVID 19 Patients - ., Prabhjot; Sethi, Jyoti (Issues and Developments in Medicine and Medical Research Vol. 2, 2022)
COVID-19 disease has affected the world with a great impact. The spectrum of disease presentation varies from asymptomatic individuals who recover without any aid to those with multi-system involvement requiring intensive care. Severity of the disease depends upon multiple factors like age, gender, associated co-morbidities, etc. The cardiovascular system being one of the target organs of SARS-CoV 2 also contributes toward significant morbidity and mortality in these patients. Autonomic imbalance associated with cardiac involvement can be easily assessed by non-invasive cardiac autonomic function tests. Objective: To assess cardiac autonomic function tests in COVID 19 patients as a possible predictor of severity of disease.